Income Distribution in Europe and the United States - Anthony Barnes Atkinson (Luxembourg Income Study (LIS), 1995)
This paper assembles and reviews empirical evidence about the personal distribution of income in Europe and makes a comparison with the United States. From his analysis, the author concludes, among other things, that: the United States has higher income inequality than Europe; within Western Europe, the Scandinavian countries, Benelux and West Germany have less inequality, Southern Europe and Ireland have higher inequality, and France, the United Kingdom, and Italy, occupy an intermediate position; differences in the distribution of income outweigh differences in average incomes: the poorest families in the United States fare less well than those in a number of European countries; and, the 'Europe-wide' distribution, viewing the European Union as an entity, is less unequal than that in the United States.
Keywords: 330